2021
DOI: 10.3389/fmolb.2020.602282
|View full text |Cite
|
Sign up to set email alerts
|

Baicalin Induces Apoptosis and Suppresses the Cell Cycle Progression of Lung Cancer Cells Through Downregulating Akt/mTOR Signaling Pathway

Abstract: Baicalin, as a natural active ingredient extracted and isolated from the traditional Chinese medicine Scutellaria baicalensis Georgi., has been potentially used in various areas for its antioxidative, antitumor, anti-inflammatory, and anti-proliferative activities. Although several studies have reported the antitumor effects of baicalin against various cancer types, its beneficial effects on lung cancer have not yet been elucidated. Therefore, the therapeutic effects and molecular mechanisms of baicalin on lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…We investigated baicalin effects on lung cancer cells proliferation and invasion. After treatment with 10, 30, 60, 90, 120, and 150 µg/ml baicalin concentrations [ 18 ] at two time points (24 h and 48 h), cell proliferation was reduced, and efficacy was dose- and time-dependent ( Figure 1b-e ). Colony formation data indicated baicalin significantly limited in vitro cell proliferation ( Figure 2a and 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…We investigated baicalin effects on lung cancer cells proliferation and invasion. After treatment with 10, 30, 60, 90, 120, and 150 µg/ml baicalin concentrations [ 18 ] at two time points (24 h and 48 h), cell proliferation was reduced, and efficacy was dose- and time-dependent ( Figure 1b-e ). Colony formation data indicated baicalin significantly limited in vitro cell proliferation ( Figure 2a and 2b ).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Baicalin has been utilized for centuries as a traditional Chinese herbal medicine for curing psoriasis, inflammation, hypertension, cardiovascular diseases, etc. [ 35 ]. Other plant species in which it is present and isolated are S. lateriflora , S. galericulata and Thalictrum baicalense [ 36 ].…”
Section: Sources and Chemistry Of Scutellaria Flav...mentioning
confidence: 99%
“… Sui et al (2020) found that 20 mg/kg of BA can trigger apoptosis and block cell cycle G1/S transition in carcinoma of the lung cells via the AKT/mechanistic target of rapamycin (mTOR) pathway. NSCLC is highly prone to invasion and metastasis, which are closely associated with the occurrence of EMT ( Xia et al, 2014 ).…”
Section: The Protection Of Ba Against Respiratory Diseasesmentioning
confidence: 99%